Lead, arsenic, cadmium and chromium contents in prioritized foods: results from portuguese total diet pilot study - Ventura, Marta (2017)
TDS provide analytical data to estimate dietary exposure of chemical contaminants. In this work was studied Pb, As, Cr and Cd profile in foods from Portuguese TDS Pilot Study. Nine hundred and twenty four foods were pooled in two hundred and thirty one laboratory samples and analysed by ICP-MS under rigorous metrological control. The highest amount (µg/kg) obtained for each chemical substance was: As 9138 ± 237 (Octopus); Pb 282 ± 5.5 (snails); Cr 605 ± 28 (Cured meat); Cd 248 ± 5 (snails). These levels of potential harmful substances do not pose a risk to population.